Visible‐Light Photocatalytic Intramolecular Cyclopropane Ring Expansion. (6th June 2017) - Luis‐Barrera, Javier; Laina‐Martín, Víctor; Rigotti, Thomas; Peccati, Francesca; Solans‐Monfort, Xavier; Sodupe, Mariona; Mas‐Ballesté, Rubén; Liras, Marta; Alemán, José
Abstract: Described herein is a new visible‐light photocatalytic strategy for the synthesis of enantioenriched dihydrofurans and cyclopentenes by an intramolecular nitro cyclopropane ring expansion reaction. Mechanistic studies and DFT calculations are used to elucidate the key factors in this new ring expansion reaction, and the need for the nitro group on the cyclopropane.